Rapid Visual Detection of Plasmodium Using Recombinase-Aided Amplification With Lateral Flow Dipstick Assay - Lin, Hong; Zhao, Song; Liu, Yanhong; Shao, Lei; Ye, Yuying; Jiang, Nizhen; Yang, Kun (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Malaria is a global public health problem. China has had no case of indigenous malaria since 2016. However, imported cases of malaria remain an issue among travelers, overseas workers, and foreign traders. Although these cases are always asymptomatic, if they donate blood, there is a great risk of transfusion transmitted-malaria (TTM). Therefore, blood banks need a rapid screening tool to detect Plasmodium species. Methods: We designed an assay using recombinase-aided amplification (RAA) and a lateral-flow dipstick (LFD) (RAA-LFD) to detect the 18S ribosomal RNA gene of Plasmodium species. Sensitivity was evaluated using a recombinant plasmid, and specificity was evaluated using DNA extracted from the blood of patients with malaria or other infectious parasites. For clinical assessment, blood samples from patients with malaria and blood donors were evaluated. Results: The RAA-LFD assay was performed in an incubator block at 37℃ for 15 min, and the amplicons were visible to the naked eye on the flow dipsticks within 3 min. The sensitivity was 1 copy/μL of recombinant plasmid. For genomic DNA from whole blood of malaria patients infected with P. falciparum, P. vivax, P. ovale, and P. malariae, the sensitivity was 0.1 pg/μL, 10 pg/μL, 10-100 pg/μL, and 100pg/μL, respectively. The sensitivity of this assay was 100pg/μL. No cross-reaction with other transfusion-transmissible parasites was detected. Conclusions: The results demonstrated that this RAA-LFD assay was suitable for reliable field detection of Plasmodium species in low-resource settings with limited laboratory capabilities.